The comparison of principals’ leadership role, teachers’ attitude and instructional needs for inclusive education in Pakistan - Khan, Tariq Mahmood (2022)
Globally, it is acknowledged that learners with diverse needs are socially more motivated in getting interacted with normal students. They get the opportunity of social inclusion through the way of inclusive education. The purpose of the current research was to compare the leadership role, principals’ and teachers’ attitudes, and the instructional need for general and inclusive education in Lahore, Pakistan. This study was based upon cognitive dissonance, functional leadership, sociocultural, and cognitive learning theories. This study was a convergent mixed methods survey research in its nature. All principals and teachers of the public girls’ and boys’ secondary schools of the city were the population of the study. The sample of 197 principals and 368 secondary school teachers was selected through multistage sampling for the quantitative study. Three principals and six secondary school teachers were selected for the qualitative study. Four tools for measuring principals’ attitude and leadership roles were self-devised, based on the literature reviewed. Likewise, four tools for measuring teachers’ attitude, and their instructional needs were developed. Further, two interview protocols; one for the principals and one for the teachers were developed to conduct in- depth interviews. The collected quantitative data was analyzed by applying inferential nonparametric statistics and the Wilcoxon and Mann Whitney test. The qualitative collected data was further analyzed through thematic analysis. The results of the study showed that principals have low perception about leadership role and attitude. Female teachers have low perception about instructional needs and attitude in inclusive education. It is suggested that the principals and the teachers need to be professionally trained in inclusive education. Besides, the government would have to change the infrastructure, technology facilities, monitor the progress system and retrain the principals and teachers for the 21st century skills in general schools in order to induct inclusive education.